2018
DOI: 10.1002/jms.4074
|View full text |Cite
|
Sign up to set email alerts
|

Screening of key odorants and anthocyanin compounds of cv. Okuzgozu (Vitis vinifera L.) red wines with a free run and pressed pomace using GC‐MS‐Olfactometry and LC‐MS‐MS

Abstract: The principal purpose of the present work is to characterize the aroma, aroma-active, and anthocyanin profiles of Okuzgozu wines and to observe the effect of the pomace pressing technique on these parameters. A total of 58 and 59 volatile compounds were identified and quantified in free-run juice wine (FRW) and pressed pomace wine (PW). Alcohols were found as the most dominant group among aroma compounds followed by esters and acids. However, among all these compounds, only 11 and 13 of them could be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Similar to the previous studies, in some wines obtained from commercial yeasts (Hasim Kelebek, Canbas, et al, 2010;Hasim Kelebek, Selli, et al, 2010;Kelebek, Canbas, et al, 2010;Tetik et al, 2018).…”
Section: General Composition Of Winessupporting
confidence: 85%
See 3 more Smart Citations
“…Similar to the previous studies, in some wines obtained from commercial yeasts (Hasim Kelebek, Canbas, et al, 2010;Hasim Kelebek, Selli, et al, 2010;Kelebek, Canbas, et al, 2010;Tetik et al, 2018).…”
Section: General Composition Of Winessupporting
confidence: 85%
“…These compounds represent 88.9% of total aroma compounds in the wine using NBY17, 90.1% in the wine using Zymaflore X5, and 88.9% in the wine obtained by spontaneous fermentation (p < .05). In a previous study, it was reported that high alcohol and esters in Öküzgözü wines are the two groups with the highest proportion of total aroma compound (Tetik et al, 2018).…”
Section: As Shown Inmentioning
confidence: 94%
See 2 more Smart Citations
“…The filtration of phenolic extracts was done using a 0.45‐μm pore size polyvinylidene fluoride membrane filter prior to analyses. Characterizing the phenolic compounds of olive oil phenolic extracts was performed by HPLC‐DAD‐ESI/MS/MS: the HPLC system was an Agilent 1100 separation module (Agilent Technologies, Palo Alto, California, USA) combined with online degasser (G1322 A, 1260 Degasser), a binary pump (G1312 B, 1260 Bin pump), and autosampler (G1367 E, 1260 HIP ALS) and linked to a diode array detector (DAD), controlled by a Windows NT‐based ChemStation software . The column applied as stationary phase was the C‐18 Phenomenex reversed‐phase (4.6 mm × 250 mm, 5 μm; Torrance, California, USA).…”
Section: Methodsmentioning
confidence: 99%